2001
DOI: 10.1016/s0014-5793(01)02579-0
|View full text |Cite
|
Sign up to set email alerts
|

Malaria parasite Plasmodium gallinaceum up‐regulates host red blood cell channels

Abstract: The properties of the malaria parasite-induced permeability pathways in the host red blood cell have been a major area of interest particularly in the context of whether the pathways are host-or parasite-derived. In the present study, the whole-cell configuration of the patch-clamp technique has been used to show that, compared with normal cells, chicken red blood cells infected by Plasmodium gallinaceum exhibited a 5^40-fold larger membrane conductance, which could be further increased up to 100-fold by raisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…The present study showed significant hemolysis of infected and oxidized cells in NaCl solution, suggesting the entry of NaCl which requires the operation of Na + ‐permeable cation channels in parallel to the Cl − channels. A low non‐selective cation conductance has been demonstrated to be activated in non‐infected human erythrocytes by oxidative stress (Duranton et al ., 2002), and increased activity of non‐selective cation channels has indeed been observed in Plasmodium ‐infected human (Desai et al ., 1996) and chicken erythrocytes (Thomas et al ., 2001).…”
Section: Discussionsupporting
confidence: 89%
“…The present study showed significant hemolysis of infected and oxidized cells in NaCl solution, suggesting the entry of NaCl which requires the operation of Na + ‐permeable cation channels in parallel to the Cl − channels. A low non‐selective cation conductance has been demonstrated to be activated in non‐infected human erythrocytes by oxidative stress (Duranton et al ., 2002), and increased activity of non‐selective cation channels has indeed been observed in Plasmodium ‐infected human (Desai et al ., 1996) and chicken erythrocytes (Thomas et al ., 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Ca 2+ signalling may transform the RBC into an active contributor to thrombosis; even if the contribution is small, it might be globally or locally relevant when occurring on top of pre-existing pathologies. Furthermore, there is growing clinical evidence in support of Ca 2+ -associated pro-thrombotic activity of RBCs in diseases such as β-thalassemia [31], [70], sickle cell disease [71], [72] or malaria [73], [74].…”
Section: Discussionmentioning
confidence: 99%
“…in the presence of serum), outwardly rectifying currents have been measured in both P. falciparum and P. berghei ‐infected erythocytes (Huber et al ., 2004; Staines et al ., 2006) but these again have different characteristics to those measured here, having time‐dependent current inactivation at negative potentials and none at high positive potentials. In addition, chicken erythrocytes infected with P. gallinaceum , although having altered electroneutral and electrogenic solute transport, do not activate VRACs (Thomas et al ., 2001; Staines et al ., 2002), even though cell swelling does induce them (note that, unlike avian erythrocytes, mammalian erythrocytes are some of the few cell types that do not activate VRACs upon cell swelling).…”
Section: Discussionmentioning
confidence: 99%